Characterization of hydrogenated dentin components by advanced 1H solid-state NMR experiments. (15th January 2021) - Coppel, Yannick; Prigent, Yann; Grégoire, Geneviève
Abstract: Collecting information about molecular organisation on biological materials such as bone and dentin represents a major challenge in attaining a better understanding of their mechanical properties. To that end, solid state Nuclear Magnetic Resonance (ssNMR) spectroscopic study is an appropriate strategy to provide atomic structural details on these amorphous composite materials. However, species like water molecules and hydroxyl groups are usually observed through 1 H magic angle spinning (MAS) ssNMR that suffers from poor resolution due to strong signal overlapping, making their identification difficult. This paper proposes a set of ssNMR experiments for 1 H characterization of the main components of human dentin, based on homo- and hetero-nuclear dipolar couplings and composed mostly of fast 1D experiments. The 1 H assignment is assisted by straightforward sample modifications: vacuum drying, deuterium exchange and demineralization. These experiments allow the hydrogen signal edition of dentin species like water molecules, HPO4 2− and OH − groups, depending on their localization (bound to the organic phase, linked to apatite or at the interface) and their dynamic behaviour. This ssNMR toolbox has the potential to provide important structural and dynamic information on chemical and physical modifications of biomaterials. Statement of Significance: Molecular characterisation of apatitic biomaterials by biophysical techniques is extremely difficult due to their complex and amorphous nature. It is, however, crucial to obtain such information if we want to understand their mechanical properties in relation to their physical state, for example their hydration levels. In this article we used a set of solid state NMR experiments and sample modifications to distinguish 1 H signal of human dentin components with a particular attention to water molecules, known for their major role in biomaterial structuring. Graphical abstract: Image, graphical abstract